SISTEMA ESPECIALISTA PARA IDENTIFICAÇÃO DE FALHAS E TOMADA DE DECISÃO - Moura, José Pinheiro de (2003)
In this work is presented the development and implementation of an Expert System to detect faults and decision making over the faults of mineral belt conveyors. This system applies artificial intelligence techniques to help the operator s decision making during the production process. It uses the CommonKADS reference methodology for knowledge acquisition and modeling. In this approach is also emphasized the difficulties in getting accurate and qualitative information, to support the decision making, and provide the users with highly trustable mechanisms able to analyze, select and drive to them the right information, meeting the demanded requisites for optimum performance during the operation of the belt conveyor.